34.6k views
1 vote
Using the distributive property simplify the expression
-2(5y + 6) + 3 - 5y

User Asra
by
5.4k points

1 Answer

1 vote

Answer:


\Huge \boxed{-15y-9}

Explanation:

To solve this problem, first you have to use the distributive property of
\displaystyle a(b+c)=ab+ac.

First, expand.


\displaystyle -2(5y+6)


-2*5=-10


\displaystyle -2*6=-12


\displaystyle -10y-12


\displaystyle -10y-12+3-5y

Next, solve.


\displaystyle -10-12+3-5=\boxed{-15y-9}

In conclusion, the correct answer is -15y-9.

User M Miller
by
5.8k points